The Implementation of Differentiated Learning Model for Primary School Students - Yuli Amaliyah; Panut Setiono (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Objective: This study aims to describe the implementation of differentiated learning in elementary schools within the framework of the independent curriculum (Kurikulum Merdeka). Method: The research employs a literature review method, analyzing and synthesizing findings from previous studies and theoretical perspectives related to differentiated learning practices in elementary education. Result: The literature review reveals several key findings: (1) Diagnostic assessments are essential to identify students’ interests, learning profiles, styles, and readiness; (2) Humanistic learning theory supports the application of differentiated learning; (3) Differentiated learning enhances student learning outcomes and engagement; (4) In science-related subjects, it positively affects students’ social skills, character development, conceptual understanding, motivation, and critical thinking; (5) It can be effectively integrated with problem-based learning models and the Pancasila Student Profile Strengthening Project (P5); (6) Successful implementation depends on teachers’ understanding of differentiated instruction, creativity, available facilities, and students’ internal factors; (70 The use of appropriate media and teaching materials enhances the effectiveness of differentiated learning. Conclusion: Differentiated learning is a viable and beneficial strategy for improving educational quality in elementary schools, particularly under the independent curriculum framework. Its success relies on proper planning, teacher preparedness, and contextual adaptation. Contribution: This study offers a comprehensive overview of how differentiated learning can be effectively implemented in elementary education. It serves as a guide for educators, curriculum developers, and policymakers to optimize teaching strategies that address the diverse needs of learners.